PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA PEMBELAJARAN FISIKA SISWA KELAS X SMA NEGERI 7 LUBUKLINGGAU - Endang Lovisia (LP4MK STKIP PGRI Lubuklinggau, 2019)
This study aims to determine student learning outcomes after the STAD learning model is applied The formulation of the problem is, What is the result of student physics learning after following the physics learning dengn Student Teams Achievement (STAD) in class X.2 SMA Negeri 7 Lubuklinggau significantly ?. This study aims to determine the results of student learning on physics learning by using Student Teams Achievement (STAD) learning model in Class X.2 SMA Negeri 7 Lubuklinggau. The research method used is Quasi Eksperimen. Population in this study all students of class X SMA Negeri 7 Lubuklinggau and as sample is class X.2 which amounts to 25 students and taken at random. Data collection is done by using test and observation techniques. Based on the result of post-test analysis of experimental class t test that thitung> ttabel or 1,883> 1,697 thus Ha accepted and H0 in decline concluded that mean of student learning result is significant